Benny Goodman concert in the United States pavilion Theater
Guests of U.S. Commissioner General Howard S. Cullman (front row center) included Admiral Alan G. Kirk (third from right, and present as a representative of Governor Averill Harriman) for the opening night performance by Benny Goodman on May 25th 1958.